Developing oral proficiency with VoiceThread: Learners' strategic uses and views. Issue 1 (13th September 2016) - Dugartsyrenova, Vera A.; Sardegna, Veronica G.
Abstract: This study explored Russian as a foreign language (RFL) learners' self-reported strategic uses of VoiceThread (VT)—a multimodal asynchronous computer-mediated communication tool—in order to gain insights into learner perceived effectiveness of VT for second language (L2) oral skills development and to determine the factors that contributed to those perceptions. The participants were eight undergraduate students who attended six weekly tutoring sessions that combined face-to-face (F2F) RFL instruction with VT activities. VT allowed them to access text-based, graphic, video, and aural linguistic input; record and store audio/video-recorded output; listen and comment on peers' recordings; and receive individualized teacher feedback on oral performance. Data from activity logs and researcher field notes were triangulated with participants' responses to two surveys and a semi-structured oral interview. Findings indicated that participants believed that VT supported their oral proficiency development through the provision of additional time and resources for independent planning, rehearsal, and controlled production of L2 forms. Most participants also agreed that VT's playback and record features were the most beneficial for developing language skills, enhancing the reflection process, and facilitating self-assessment and creativity in the L2. Yet, despite VT's multimodal affordances and the availability of communicative tasks via VT, participants did not perceive VT as a social environment that could promote peer-to-peer interaction or replace F2F communication. A thematic data analysis suggested that participants' preferences for language learning tasks influenced their strategic uses of VT's features, which ultimately affected their perceptions of VT's value for promoting meaningful language learning interactions. Pedagogical considerations are discussed.